Alternatif Penyelesaian Sengketa Di Luar Pengadilan Serta Kelebihan Dan Kelemahannya - Andi Candra; Warmiyana Zairi Absi (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2021)
The court is not authorized to re-examine a case where the award of arbitration has been passed unless there is an unlawful act related to making an arbitration decision in good faith, and if the arbitral award violates public order. The advantage is that the confidentiality of disputes between the parties is guaranteed, delays can be avoided due to procedural and administrative matters and weaknesses, the arbitration award is very dependent on the technical ability of the arbitrator to provide satisfactory decisions to both parties. Because even though the arbitrator is an expert, it may not necessarily satisfy the parties.